Periodontal regeneration employing gingival margin‐derived stem/progenitor cells in conjunction with IL‐1ra‐hydrogel synthetic extracellular matrix. (May 2015) - Fawzy El‐Sayed, Karim M.; Mekhemar, Mohamed K.; Beck‐Broichsitter, Benedicta E.; Bähr, Telse; Hegab, Marwa; Receveur, Jan; Heneweer, Carola; Becker, Stephan T.; Wiltfang, Joerg; Dörfer, Christof E.
Abstract Aim This study investigated the periodontal regenerative potential of gingival margin‐derived stem/progenitor cells (G‐MSCs) in conjunction with IL‐1ra‐releasing hyaluronic acid synthetic extracellular matrix (HA‐sECM). Materials and Methods Periodontal defects were induced at four sites in eight miniature pigs in the premolar/molar area (−4 weeks). Autologus G‐MSCs were isolated from the free gingival margin and magnetically sorted, using anti‐STRO‐1 antibodies. Colony formation and multilineage differentiation potential were tested. The G‐MSCs were expanded and incorporated into IL‐1ra‐loaded/unloaded HA‐sECM. Within every miniature pig, four periodontal defects were randomly treated with IL‐1ra/G‐MSCs/HA‐sECM (test group), G‐MSCs/HA‐sECM (positive‐control), scaling and root planing (SRP; negative control‐1) or left untreated (no‐treatment group; negative control 2). Differences in clinical attachment level (ΔCAL), probing depth (ΔPD), gingival recession (ΔGR), radiographic defect volume (ΔRDV), and changes in bleeding on probing (BOP) between baseline and 16 weeks post‐transplantation, as well as periodontal attachment level (PAL), junctional epithelium length (JE), connective tissue adhesion (CTA), cementum regeneration (CR) and bone regeneration (BR) at 16 weeks post‐transplantation were evaluated. Results Isolated G‐MSCs showed stem/progenitor cell characteristics. IL‐1ra loaded and unloaded G‐MSCs/HA‐sECM showed higher ΔCAL, ΔPD, ΔGR, PAL, CR and BR as well as a lower JE compared to their negative controls and improved BOP. Conclusion G‐MSCs in conjunction with IL‐1ra‐loaded/unloaded HA‐sECM show a significant periodontal regenerative potential.